We are okay - LaCour, Nina (New York : Dutton Books, an imprint of Penguin Random House LLC, 2016)
"From the award-winning author ofHold Still comes an achingly beautiful novel about grief and the enduring power of friendship. "Exquisite." -Kirkus, starred review "LaCour paints a captivating depiction of loss, bewilderment, and emotional paralysis. raw and beautiful."-Booklist, starred review "Beautifully crafted. A quietly moving, potent novel."-School Library Journal, starred review "A moving portrait of a girl struggling to rebound after everything she's known has been thrown into disarray."- Publishers Weekly, starred review You go through life thinking there's so much you need. Until you leave with only your phone, your wallet, and a picture of your mother. Marin hasn't spoken to anyone from her old life since the day she left everything behind. No one knows the truth about those final weeks. Not even her best friend Mabel. But even thousands of miles away from the California coast, at college in New York, Marin still feels the pull of the life and tragedy she's tried to outrun. Now, months later, alone in an emptied dorm for winter break, Marin waits. Mabel is coming to visit and Marin will be forced to face everything that's been left unsaid and finally confront the loneliness that has made a home in her heart. An intimate whisper that packs an indelible punch, We Are Okay is Nina LaCour at her finest. This gorgeously crafted and achingly honest portrayal of grief will leave you urgent to reach across any distance to reconnect with the people you love"--
"After picking up and leaving everything behind in California, eighteen-year-old Marin, with the help of her former friend, must confront her grief and the truths that caused her to flee her home"--
Michael L. Printz Award for Excellence in Young Adult Literature, 2018
Keywords: College students -- Juvenile fiction; Grief -- Juvenile fiction; Friendship -- Juvenile fiction; Lesbian teenagers -- Juvenile fiction; College students -- Fiction; Grief -- Fiction; Friendship -- Fiction; College students -- Fiction; Friendship -- Fiction; Loneliness -- Fiction; Orphans -- Fiction; Grief -- Fiction; Grandfathers -- Fiction; Colleges and universities -- Fiction; Lesbians -- Fiction